Clonal spread and antibiotic selection of a mutation preventing the evolution of high-level resistance: Supporting information - Jagdmann, Jennifer (Uppsala University, 2022)
Data on clonal spread and antibiotic selection of a mutation preventing the evolution of high-level resistance. Datafiles consists of:
Dataset S1: Primary data for figures and tables.
Table S2: Frequency and phenotype of TGC resistant mutants selected at TGC 0.5 mg/L.
Table S4: Lineages, MICs of mutants, and mutations found following selection of mutants at TGC 1 or 2 mg/L and following step-wise selection of mutants in presence of increasing TGC concentrations.
Table S8: Characterisation of tet(A)-carrying isolates from NCBI.
Table S10: Strains used in the study.
Table S11: Primers used in the study.

The dataset was originally published in DiVA and moved to SND in 2024.
Clonal spread and antibiotic selection of a mutation preventing the evolution of high-level resistance: Supporting information
Keywords: drug resistance; läkemedelsresistens; antibiotics; antibiotika; antibiotic resistance; antibiotikaresistens; Microbiology; Mikrobiologi